Estudo de um modelo animal de alergia e sua supressão pela infusão com Imunoglobulinas Policlonais - Guilherme Gusmao Silva (2012)
Allergic patients maintain high levels of allergen specific IgE, and highertiters of total IgE than the average of the normal population. In contrast,experimental models for induction of IgE in rodents usually results in a transient synthesis of IgE that cannot be secondary stimuli. In the year 1970, Vaz and Levine showed that a persistent formation of IgE can be obtained by intermittent immunization of high-responders mice strains with low doses of antigen. The mechanism of this persistent IgE synthesis that mimics the human clinical situation is unknown.Recently, it was hypothesized that persistent IgE synthesis is derived from an oligoclonal expansion of CD4+ T lymphocytes. This oligoclonal expansion could be minimized by treatment with high doses of polyclonal immunoglobulins, a treatment known as IVIg, as used in human and experimental asthma. We studied three different strains of mice high responders to ovalbumin (OVA) intermittently immunized with low doses of antigen with aluminum hydroxide as adjuvant. As expected these animals developed persistent synthesis of IgE with different levels. It was also tested for sensitivity tested by allergic pulmonary aerosol OVA assessed by the cellular infiltration in the bronchi. Treatment with IVIg had no significant effect on the synthesis of IgE however, had a clear inhibitory effect on the cellular infiltrate (total and eosinophilic) resulting fromthe aerosol challenges with OVA as well as on the level of IL-5 in lung tissue